A comparative examination of dietary sodium content in bread and its public consumption pattern in Muscat, Oman. Issue 1 (14th August 2019) - AbuKhader, Majed; Abdelraziq, Rawan; Al-Azawi, Maryam; Ali, Salma Khamis
Abstract : Purpose: This paper aims to examine and assess the sodium content in various pre-packed bread products marketed in three cities, Muscat, Morgantown (West Virginia) and Stockholm, and in combination with spread products. It also aims to investigate the pattern of public consumption of bread in Muscat. Design/methodology/approach: A random cross-sectional investigation was followed. This study used the nutrition panel of selected bread and spread products to record sodium content and a close-ended questionnaire. Findings: The mean sodium content in 100 g of bread marketed in Muscat was significantly lower than that in Morgantown ( p  < 0.001) and Stockholm ( p  < 0.022). The intake of 100 g of any bread type with 40 g of cheese spread will offer more than 20 per cent of the recommended daily intake of sodium, which poses a health risk upon frequent consumption. Results from the survey conducted in Muscat showed that most of the people consume bread in breakfast and the average amount of bread consumed per day was reported to be 100 g. Only 74.9 per cent of the participants knew that salt is added in the making of bread. Originality/value: This research is of a value to food policymakers in relation to the use of salt (sodium) in bread. Sodium content in bread products varied significantly in the selected markets. Daily consumption of bread with cheese spreads should be either reduced or avoided by children because of high sodium content. Average intake of 100 g bread per day by participants in the survey is an indicator of a reduced exposure to sodium.